Vienna 8: the mediterranean fruit fly strain that will be used in the biofabrica Mocamed Brazil, in Juazeiro-BA. - PARANHOS, B. A. J. (2004)
The objective of this work is to describe the steps to rear Vienna 8, the most recent and productive strain, which will be released in the irrigated fruit crop of semi-árid, to suppress C. capitata population.